2011
DOI: 10.1016/j.jprot.2011.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and interactome analysis of Trypanosoma cruzi Tryparedoxin 1

Abstract: Trypanosoma cruzi tryparedoxin 1 (TcTXN1) is an oxidoreductase belonging to the thioredoxin superfamily, which mediates electron transfer between trypanothione and peroxiredoxins. In trypanosomes TXNs, and not thioredoxins, constitute the oxido-reductases of peroxiredoxins. Since, to date, there is no information concerning TcTXN1 substrates in T. cruzi, the aim of this work was to characterize TcTXN1 in two aspects: expression throughout T. cruzi life cycle and subcellular localization; and the study of TcTXN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 47 publications
(60 reference statements)
2
30
0
1
Order By: Relevance
“…The increase in tryparedoxin perdoxidases occurred in infective trypomastigote and replicative amastigote stages irrespective of the cell types (e.g., muscle cells in this study, and LLC-MK2 and macrophages in other studies [34,50]) used for culturing the parasites. Regeneration of the reduced TXNPx depends on cytosolic (TXN I)-and membrane (TXN II)-localized thioredoxin substrates (31,51). Consistent with the increased abundance of TXNPx, the TXN I level was also increased in COL and SYL trypomastigotes (Fig.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The increase in tryparedoxin perdoxidases occurred in infective trypomastigote and replicative amastigote stages irrespective of the cell types (e.g., muscle cells in this study, and LLC-MK2 and macrophages in other studies [34,50]) used for culturing the parasites. Regeneration of the reduced TXNPx depends on cytosolic (TXN I)-and membrane (TXN II)-localized thioredoxin substrates (31,51). Consistent with the increased abundance of TXNPx, the TXN I level was also increased in COL and SYL trypomastigotes (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…Parasite lysates were probed by using antibodies against cytosolic (cTXNPx) and mitochondrial (mTXNPx) isoforms of tryparedoxin peroxidase, tryparedoxin isoforms TXN I and TXN II, and iron superoxide dismutase isoforms FeSODa and FeSODb (31,32). Due to the finding of a differential abundance of ␣-tubulin and ␤-actin in T. cruzi isolates (Table 1 and Table 2), we could not use these proteins for normalizing the antioxidant protein content.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dada su relevancia en los mecanismos de evasión de la respuesta inmunitaria, estas enzimas se han considerado factores de virulencia importantes y están siendo objeto de estudio para utilizarlas en el diseño racional de fármacos (21). En un estudio de análisis de expresión diferencial entre parásitos obtenidos a partir de un caso agudo comparados con los de uno crónico, obtenidos en la zona endémica de Santander en Colombia, se encontró sobreexpresión de la peroxidasa triparredoxina, la cual podría estar asociada con el desarrollo de la forma aguda de la enfermedad (22).…”
Section: Resultsunclassified
“…4.4.3 for T(SH) 2 and TRYR). Previous studies have demonstrated that TXNs function as electron donors for the Prxs required for ROS metabolism, DNA and protein synthesis through protein-protein interactions, thus making them essential for parasite survival (Piñeyro et al 2011;Flohé 2012). Four TXN homologous genes have been found in Euglena, with three isoforms being predicted to be localized in the cytosol and the other in mitochondria (Table 4.1, Fig.…”
Section: The Thioredoxin Superfamily Proteinsmentioning
confidence: 98%